Pengaruh Pelatihan Bassic Life Support Terhadap Kesiap Siagaan Perawat Instalasi Gawat Darurat (IGD) RSUD Patut Patuh Patju Gerung - Indra Arianto; Arlan Fikriadi (Journal of Nursing Perspectives, 2025)
Nurses in EDs should be able to respond fast and appropriately when life threatening conditions such as cardiac arrest occur in order to avoid morbidity and mortality. Introduction Basic Life Support (BLS) skills provide essential knowledge to the nurses, which is critical in effective initial resuscitation until advanced care is achieved. But even ready when we are no longer in regular practice and there has been little updating of clinical skills. The purpose of the study was to determine the effect of Basic Life Support training on emergency nurse readiness at RSUD Patut Patuh Patju Gerung. The current study utlilised a quasi-experimental design with pretest-posttest and included all of the ED nurses who were eligible. Preparedness included surveyed perceptions on knowledge, initial response, technical skills and perceived readiness as well as direct observation of psychomotor skill using a standardized list. The intervention included theoretical teaching sessions, teacher demonstrations, practice, and simulated emergencies under the guidance of certified trainers. Data was statistically analyzed by paired t test (p < 0.05). Results The results showed improvement in preparedness for the full group after training (overall knowledge score, compression quality, AED placement and coordinated performance during simulated CPR). Participants also felt more confident in dealing with cardiac arrest, and simulation was considered to be the most helpful training modality for improving preparedness. These findings suggest that being trained in BLS has an effect on nurses' preparedness for emergency care provision and as such emphasizes the need for structured ongoing professional development courses within hospital emergency units. It is recommended that regular training, retraining and refresher courses should enhance the resuscitation abilities of staff towards better patient safety using good quality emergency care services.